ANALISIS KESALAHAN BERBAHASA INDONESIA PADA SKRIPSI MAHASISWA PROGRAM STUDI SISTEM INFORMASI SEKOLAH TINGGI MANAJEMEN INFORMATIKA DAN KOMPUTER (STMIK) KHARISMA MAKASSAR - Sukmawaty Sukmawaty (Universitas Negeri Makassar, 2017)
Abstract: Error Analysis In The Indonesian Language In Students’ Thesis Of Information System Of Study Program At Kharisma Makassar. The research aims at describing the Indonesian language errors in the students’ thesis of information system study program. The population was the students’ thesis of information system study program at Kharisma Makassar consisting of 486 theses. The sample taken was 50 theses. Based on the findings, the research can be concluded that the language errors found in the students’ thesis of information system study program at Kharisma Makassar were the use of capital letters, italics, and punctuation. In addition, the language errors in using words, constructing sentence, making paragraph were also found. The most errors were the use of italics (98%), whereas the fewest errors were the form of paragraph (16%).